Project ARTISAN : exploring the effects of an Intergenerational arts-based intervention on Singaporean youth empowerment and loneliness - Tew, Weicong (2019)
Objectives: This study seeks to explore if a 5-week intergenerational arts-based intervention combining art-making, facilitated story-telling, curated museum visits and reflective writing titled Project ARTISAN can tackle youth loneliness and powerlessness in Singapore by empowering local youths. Methods: A battery of psychometric assessments was administered at three timepoints to 18 youths who were part of the intervention group of the study and then analysed using a Wilcoxon Signed Rank test. The transcripts from group discussions and focus groups they took part in were also utilized for analysis through a thematic analysis with a grounded theory approach. Findings: Analysis of the quantitative results from baseline to post-intervention revealed that the intervention produced statistically significant improvements in Satisfaction with Life, Quality of Life, Emotional Support, Loneliness, Ego-Resilience and Repertoire of Problem-Solving strategies. However, Ego-Resilience and Repertoire of Problem-Solving Strategies were unable to sustain the increase and fell back to baseline levels 5-weeks post-intervention.No significant improvement in Social Connectedness was recorded at any time point. Qualitative analysis yielded insights into how Empowerment is created within the Individual and translated to Community Empowerment, leading to the theorizing of an Individual-Community Empowerment (ICE) Model. Results from both quantitative and qualitative analysis come together to provide insights into how Project ARTISAN can tackle loneliness through an increase in individual and communal empowerment.